Associations between perceived value of exclusive breastfeeding among pregnant women in the United States and exclusive breastfeeding to three and six months postpartum: a prospective study. Issue 1 (December 2016) - Nnebe-Agumadu, Uche; Racine, Elizabeth; Laditka, Sarah; Coffman, Maren
Abstract Background Successful breastfeeding often starts with prenatally established intention. Yet, few mothers with the intention to exclusively breastfeed achieve their intended breastfeeding duration goal. This study examined the degree to which having a strong value of exclusive breastfeeding is associated with exclusive breastfeeding duration for at least 3 and 6 months postpartum among women who reported prenatal intention to exclusively breastfeed. Methods Data were from the Infant Feeding Practices Study II, a longitudinal US national survey that followed maternal-infant dyads from pregnancy to 1 year postpartum. Bivariate and multivariate regression examined the degree to which strong maternal value of exclusive breastfeeding predicted exclusive breastfeeding duration. Results Of the 1799 women who prenatally intended to exclusively breastfeed within the first few weeks postpartum, 34 and 9 % exclusively breastfed for at least 3 months and 6 months, respectively. Thirty-six percent of women reported strongly valuing exclusive breastfeeding out of which 46 % exclusively breastfeed to three months. In adjusted results, women who reported that they strongly value exclusive breastfeeding had more than twice the odds of exclusive breastfeeding for at least 3 months (Adjusted Odds Ratio [AOR] 2.29; 95 % confidence interval [CI] 1.84, 2.85) and for 6 months (AOR 2.49; 95 % CI 1.76, 3.53) compared to those who did not strongly value exclusive breastfeeding. Conclusion Valuing the benefits of exclusive breastfeeding during pregnancy is a strong independent predictor of actual exclusive breastfeeding duration. A minority of pregnant women strongly value exclusive breastfeeding and are able to exclusively breastfeed to 3 months even among women with established prenatal intention to exclusively breastfeed. Prenatal maternal education and environmental lactation support that extends into the postnatal period can promote longer duration of exclusive breastfeeding.